2009
DOI: 10.1097/jgp.0b013e31818f3a6b
|View full text |Cite
|
Sign up to set email alerts
|

Depressive Symptoms Moderate the Influence of the ApolipoproteinE ɛ4 Allele on Cognitive Decline in a Sample of Community Dwelling Older Adults

Abstract: Objectives-The APOE ε4 allele and a history of depression are each separate risk factors for cognitive decline (CD). However, little research has investigated whether a history of depression influences the relationship between APOE ε4 and CD. The present study examined whether depressive symptoms had greater influence on subsequent CD among participants with APOE ε4 than those without the allele. Design-Prospective six year longitudinal study. Setting-Community in-home interviews. Participants-A biracial sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
32
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 48 publications
0
32
1
Order By: Relevance
“…In a cohort of older persons with normal cognitive function, a synergistic interaction was found between depression and APOE e4 on incidence of mild cognitive impairment (Geda et al, 2006). In another cohort with cognitively normal elders, the association between depressive symptoms and cognitive decline was stronger among participants with APOE e4 (Corsentino et al, 2009).…”
Section: Discussionmentioning
confidence: 97%
“…In a cohort of older persons with normal cognitive function, a synergistic interaction was found between depression and APOE e4 on incidence of mild cognitive impairment (Geda et al, 2006). In another cohort with cognitively normal elders, the association between depressive symptoms and cognitive decline was stronger among participants with APOE e4 (Corsentino et al, 2009).…”
Section: Discussionmentioning
confidence: 97%
“…Carriers of the APOE e4 allele show worse cognitive test performance (3) and increased cognitive decline over time (4)(5)(6). There is mounting evidence to suggest that the effects of depressive symptoms and APOE combine to accelerate cognitive decline in old age (7,8). However, existing studies have been underpowered to investigate this at the genotype level and have focused on depressive symptoms rather than clinically defined depression.…”
Section: Introductionmentioning
confidence: 97%
“…2,3 Several studies have reported that depression was associated with faster cognitive decline in carriers of the APOE-ε4 allele, a genetic marker for AD, compared to those without this genetic marker. 5,6 Depression may raise the risk of dementia because of biologic abnormalities associated with this affective illness, such as hypothalamic-pituitary axis dysregulation and high cortisol levels 7 , decreased homeostasis of the autonomic nervous system resulting in decreased heartrate variability 8 , increased platelet activation 9 , and an increase in pro-inflammatory factors. 10 Depression may also increase the risk of dementia because of its association with a higher risk for behavioral risk factors such as smoking, obesity, and sedentary lifestyle and vascular risk factors such as hypertension, hyperlipidemia, and diabetes.…”
mentioning
confidence: 99%